Ice melting can change DMSP production and photosynthetic activity of the haptophyte Phaeocystis antarctica - Kameyama, S; Otomaru, M; McMinn, A; Suzuki, K (Journal of Phycology, 2020)
Phaeocystis antarctica is an important primary producer in the Southern Ocean and plays roles in sulfur cycles through intracellular production of dimethylsulfoniopropionate (DMSP ), a principal precursor of dimethyl sulfide (DMS ). Haptophytes, including P. antarctica, are known to produce more DMSP than other phytoplankton groups such as diatoms and green algae, suggesting their important contribution to DMS concentrations in the Southern Ocean. We assessed how sea ice formation and melting affect photosynthesis and DMSP accumulation in P. antarctica both in seawater and in sea ice. Incubations were undertaken in an ice tank, which simulated sea ice formation and melting dynamics. The maximum quantum yield of photochemistry ( F v / F m ) in photosystem II , as estimated from pulse‐amplitude‐modulated (PAM ) fluorometry, was generally higher under low‐light conditions than high‐light conditions. Values of F v / F m , the relative maximum electron rate (rETR max ), and photosynthetic efficiency (α) were lower in sea ice than in seawater, implying reduced photosynthetic function inside the sea ice. The reduction in photosynthetic function was probably due to the hypersaline environment in the brine channels. Total DMSP (DMSP t) concentration normalized by chlorophyll‐ a concentration was significantly higher in the sea ice than in the other environments, suggesting high accumulation of DMSP , probably due to its osmotic properties. F v / F m , specific growth rate, and DMSP t concentrations decreased with decreasing salinity with the lowest values found at a salinity of 22, that is, the lowest salinity tested. These results suggest that sea ice melting is responsible for a reduction in growth rate and DMSP production of P. antarctica .